Influencing Factors of Red Chillies Productio in Maligas Bandar, Simalungun Regency - Nurma Ani; Mazlina; Try Koryati; Rosmaiti (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of this study was to investigate the factors that affect red chili farming's income in the village of Maligas Bandar, Simalungun Regency. This study's population consisted of forty red chili farmers. Quantitative descriptive research was used in this study. The results found in this research variable influence the production of red chili significantly in Maligas Bandar Village, Gunung Malela District, Simalungun Regency. According to the findings of the analysis, the variable land area (X1), seeds (X2) and fertilizer (X3) had a significant impact on the production of red chili or the variable (Y). The results of the calculation of R2 explain 0.850% or 85%. While the remaining 25% are variables not included in this study.